PENERAPAN MODEL ARBITRAGE PRICING THEORY DENGAN PENDEKATAN VECTOR AUTOREGRESSION DALAM MENGESTIMASI EXPECTED RETURN SAHAM (Studi Kasus: Saham-Saham Kompas100 Periode 2010-2013) - AYUNING TYAS, VIAN RISKA; DHARMAWAN, KOMANG; ASIH, MADE (E-Jurnal Matematika; Vol 3 No 1 (2014)DO - 10.24843/MTK.2014.v03.i01.p061, 2014)
The Arbitrage Pricing Theory (APT) is an alternative model to estimate the price of securities based of arbitrage concept. In APT, the returns of securities are affected by several factors. This research is aimed to estimate the expected returns of securities using APT model and Vector Autoregressive model. There are ten stocks incorporated in Kompas100 index and four macroeconomic variables, these are inflation , exchange rates, the amountof circulate money (JUB), and theinterest rateof Bank Indonesia(SBI) are applied in this research. The first step in using VAR is to test the stationary of the data using colerogram and the results indicate that all data are stationary. The second step is to select the optimal lag based on the smallest value of AIC. T he Granger causality test shows that the LPKR stock is affected by the inflation and the exchange rate while the nine other stocks do not show the existence of the expected causality. The results of causality test are then estimated by the VAR models in order to obtain expected returnof macroeconomic factors. The expected return of macroeconomic factors obtained is used in the APT model, then the expected return stock LPKR is calculated. It shows that the expected return of LPKR is 3,340%
Keywords: Arbitrage Pricing Theory, Granger causality test, optimal lag test, Portmanteau test, stationary test, Vector Autoregression